Fabrication of gold nanoparticles in water by laser ablation technique and their characterization - Haider, A F M Yusuf; Sengupta, S.; Abedin, Kazi Monowar; Talukder, Aminul (© 2011 Springer-Verlag., 2017)
This article was published in the Journal Applied Physics A: Materials Science and Processing [© 2011 Springer-Verlag] and the definite version is available at : 10.1007/s00339-011-6542-6